Fabrication of Nanopillar-Based Split Ring Resonators for Displacement Current Mediated Resonances in Terahertz Metamaterials - Liu, Chao (J Vis Exp, 2017)
Terahertz (THz) split ring resonator (SRR) metamaterials (MMs) has been studied for gas, chemical, and biomolecular sensing applications because the SRR is not affected by environmental characteristics such as the temperature and pressure surrounding the resonator. Electromagnetic radiation in THz frequencies is biocompatible, which is a critical condition especially for the application of the biomolecular sensing. However, the quality factor (Q-factor) and frequency responses of traditional thin-film based split ring resonator (SRR) MMs are very low, which limits their sensitivities and selectivity as sensors. In this work, novel nanopillar-based SRR MMs, utilizing displacement current, are designed to enhance the Q-factor up to 450, which is around 45 times higher than that of traditional thin-film-based MMs. In addition to the enhanced Q-factor, the nanopillar-based MMs induce a larger frequency shifts (17 times compared to the shift obtained by the traditional thin-film based MMs). Because of the significantly enhanced Q-factors and frequency shifts as well as the property of biocompatible radiation, the THz nanopillar-based SRR are ideal MMs for the development of biomolecular sensors with high sensitivity and selectivity without inducing damage or distortion to biomaterials. A novel fabrication process has been demonstrated to build the nanopillar-based SRRs for displacement current mediated THz MMs. A two-step gold (Au) electroplating process and an atomic layer deposition (ALD) process are used to create sub-10 nm scale gaps between Au nanopillars. Since the ALD process is a conformal coating process, a uniform aluminum oxide (Al(2)O(3)) layer with nanometer-scale thickness can be achieved. By sequentially electroplating another Au thin film to fill the spaces between Al(2)O(3) and Au, a close-packed Au-Al(2)O(3)-Au structure with nano-scale Al(2)O(3) gaps can be fabricated. The size of the nano-gaps can be well defined by precisely controlling the deposition cycles of the ALD process, which has an accuracy of 0.1 nm.